Farsi document image recognition system using word layout signature - Ergun, Cem; Norozpour, Sajedeh (Tubitak Scientific & Technological Research Council Turkey, 2019)
In this paper, a new representation of Farsi words is proposed to present the keyword spotting problems in Farsi document image retrieval. In this regard, we define a signature for each Farsi word based on the word connected component layout. The mentioned signature is shown as boxes, and then, by sketching vertical and horizontal lines, we construct a grid of each word to provide a new descriptor. One of the advantages of this method is that it can be used for both handwritten and machine-printed texts. Finally, to evaluate the performance of our system in comparison to other methods, a database that contains 19,582 printed Farsi words is examined, and after applying this approach, a recall rate of 98.1% and a precision rate of 94.3% are obtained.
Keywords: Farsi document image retrieval; word spotting; word layout signature; optical character recognition